COVID-19 Enforced Shift to Distance Education: Readiness and Challenges - Alshaboul, Yousef; Hamaidi, Diala; Arouri, Yousef; Alshaboul, Asia (Journal of Education and e-Learning Research, 2021)
The COVID-19 pandemic has forced a worldwide revolution in our understanding of how to conduct education. International lockdowns were the catalyst for a global shift from traditional face-to-face learning to distance learning. This comparative study utilized a mixed method approach to investigate the readiness of Higher Education instructors and students and the challenges arising from the shift to distance education in two different Arab countries, Qatar and Jordan. Generally, the findings gleaned from the questionnaires (230 instructors and 551 students) revealed certain inconsistencies with the findings that emerged from the interviews (18 instructors and 38 students) in terms of both the level of readiness and the challenges faced. The results showed a substantial variation in instructors and students’ readiness at both participating universities. While factors like country, age, gender, specialization, years of experience/year in the program, and the number of online training courses prior to the COVID-19 epidemic proved to cause statistically insignificant differences in instructors and students’ readiness, variables including age, gender and prior experience in online courses were relatively influential for students in terms of the challenges they faced.